2023
DOI: 10.1002/jad.12142
|View full text |Cite
|
Sign up to set email alerts
|

What are the predictors of sexting behavior among adolescents? The positive youth development approach

Abstract: Introduction: Research supporting adolescent sexual health and empowerment is needed. The study investigates sexting among adolescents using the resources that characterized the Positive Youth Development Approach (PYD) and considering the impact of parental monitoring. The study aims to describe sexting among three different groups of adolescents (i.e., Non Sexters [NS], Passive Sexters [PS], and Active Sexters [AS]) considering age and sex (first aim). It also seeks to identify predictors among the PYD's res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…However, they are in line with the literature Davis, et al, 2016;Bianchi et al, 2016Bianchi et al, , 2017Liong & Cheng, 2019). Indeed, according to the framework of the Positive Youth Development Approach (PYD) and to the recent perception of sexting as a path of behavior which describes adolescents' development, youths could explore their sexuality through sexting and improve their understanding of their feelings related to their body image (Pistoni et al, 2023), using sexting to approach sexuality for the rst time, or to explore their sexuality within their relationship (Kosenko et al, 2017).…”
Section: Principal Ndingssupporting
confidence: 72%
See 1 more Smart Citation
“…However, they are in line with the literature Davis, et al, 2016;Bianchi et al, 2016Bianchi et al, , 2017Liong & Cheng, 2019). Indeed, according to the framework of the Positive Youth Development Approach (PYD) and to the recent perception of sexting as a path of behavior which describes adolescents' development, youths could explore their sexuality through sexting and improve their understanding of their feelings related to their body image (Pistoni et al, 2023), using sexting to approach sexuality for the rst time, or to explore their sexuality within their relationship (Kosenko et al, 2017).…”
Section: Principal Ndingssupporting
confidence: 72%
“…is nding leads to the possible interpretation that early adolescents are exploring their sexuality in a protected context. From this standpoint, as posited by the concept of Positive Youth Development (Pistoni et al, 2023), sexting can be conceptualized as the modern manner that adolescents express their sexuality in the digital age (Yépez-Tito et al, 2020), as well as in intimate communication facilitated by technology.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, if young people worry too much without having the necessary tools to manage their emotions, they may end up suffering. Regarding the relationship of the 5Cs and risk behaviors, high levels of positive relationships with others (Connection) were shown to be protective of several risk behaviors such as engaging in sexting and substance abuse [52,64].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, in a study, it was found that high Youth 2024, 4 levels of Character and Connection were associated with lower risk behaviors such as substance abuse and delinquency, while high levels in the Confidence dimension was related to participation in these types of behaviors [52]. On the other hand, an investigation focused on the relationship of the 5Cs, sexting and parental control [64] showed that those adolescents who had a good view of themselves (Competence) and low presence of moral standards (Character) participated more in sexting. The social relationships one had with others (Connection) also played an important role, as those who were more isolated were the ones who participated more in active sexting.…”
Section: The Relationship Between the 5cs And Psychological Adjustmentmentioning
confidence: 99%